Encryption of Information on Brain Tumor Images Using Vigenere Cipher Algorithm and Least Significant Bits - Burjulius, Renol; Rohmayani, Dini; Lena, Sonty (LPPM Universitas Dian Nuswantoro, 2023)
Cryptography is a branch of existing methods in mathematics which has the goal of being able to maintain the confidentiality of the information contained in the data so that the information is not known by parties who have no interest. Confidentiality of this information is important so that the information sent is not misused irresponsibly. Vigenere Cipher is a method used for cryptography. Vigenere Cipher works by using a tabula recta table where the table contains an alphabet arranged based on the Caesar Cipher shift. In this study, the Vigenere Chiper algorithm will be used to encrypt information into 25 brain tumor images. In the tests carried out on 25 images, the best MSE obtained was 1.541e-05, while the best PSNR was 48.1219, for the best SSIM it was 0.99995, then for the BER value, all images obtained a BER value of 0 and also for the entropy of the best steganography image, which was 6.8204.